DZIAŁANIA KOŚCIOŁA RZYMSKOKATOLICKIEGO W POLSCE W ZAKRESIE OCHRONY ZABYTKÓW - Zbigniew Czernik (Ochrona Dziedzictwa Kulturowego)
It has always been of tremendous importance for Latin Church to protect and preserve cultural heritage which it has been collecting and creating for ages. Particular attention is therefore paid to take care of, preserve, and conserve historic monuments and sites as well as to ensure they hold the right place in cult and liturgy. In the past, this approach was reflected not only in documents produced by church (both general and particularistic ones) but also in carrying out works to historic monuments and sites. Church in Poland has always aimed its actions at providing monuments and sites with good care. Participants of the Polish Episcopal Conference and members of Diocesan Synods made a considerable number of legal regulations. A church system of historic preservation service has been developed for years; an abundance of works are carried out to historic monuments and sites; there are church institutions collecting and listing properties and sites as well as supervising protection-related activities and cooperating with selected government bodies.